Ecodesign and environmental assessment: a synergy for higher education institutions - Swe, Wint Mon; Ribau Teixeira, Margarida; Smuleac, Laura; Nunes, Luís M. (Frontiers in Sustainability, 2025)
This article explores how ecodesign can help enhance environmental assessment methods (EAMs) employed by Higher Education Institutions (HEIs). Current EAMs primarily offer resource management evaluations or sustainability rankings but lack holistic and actionable solutions for institutional improvements. The proposed method integrates ecodesign tools, such as Life Cycle Assessments (LCA), environmental benchmarking, and parametric design tools, with existing EAM frameworks. This synergy allows HEIs to quantitatively assess their environmental and social impacts while identifying targeted strategies for improvement. By embedding ecodesign into institutional practices the approach provides a structured pathway to align HEIs with global sustainability goals, fostering innovation and continuous improvement. The paper emphasizes a multi-tool integration strategy, offering a cohesive solution to advance sustainability comprehensively within HEIs.